2013
DOI: 10.1007/s10735-013-9533-4
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen deficiency reduces the dentinogenic capacity of rat lower incisors

Abstract: Endogenous estrogen deficiency usually causes the systemic osteoporosis including the jaw bones. However, it remains unclear whether estrogen deficiency can affect the tooth mineralization. In this study, the classical osteoporotic rat model was established via the ovariectomy, which was subsequently confirmed by the detection of serum estradiol levels and body weights. The mineralization-related assays were performed to observe the potential changes in mineralized tissues of rat lower incisors. The clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 48 publications
(57 reference statements)
2
19
0
2
Order By: Relevance
“…, Xu et al . ). Furthermore, in the NMP‐treated group (OVX NMP), DSP expression was clearly preserved and had a similar staining intensity to the Sham Veh group (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…, Xu et al . ). Furthermore, in the NMP‐treated group (OVX NMP), DSP expression was clearly preserved and had a similar staining intensity to the Sham Veh group (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Earlier studies have demonstrated that pre-dentine can provide a supporting mechanical function for the pulp tissue (Xu et al 2014). Additionally, the pre-dentine layer thickness directly correlates with the dentinogenic activity function in human teeth (Couve 1987).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations